Economic Analysis of Biochar Use in Soybean Production in Poland - Agnieszka Ewa Latawiec (MDPI AG, 2021)
Soybean (Glycine max L.) is one of the most important crops grown globally. Biochar has been proposed as an alternative to aid sustainable soybean production. However, comprehensive studies that include both the economic aspects of soybean production and biochar are scarce. Poland, with an economy largely based on agriculture, is an interesting case to investigate the cost-effectiveness of using biochar in soybean production. We show that the use of biochar at rates of 40, 60 and 80 t/ha is unprofitable compared with a traditional soil amendment, such as NPK fertilization. The breakeven price for biochar to be economically viable should be USD 39.22, USD 38.29 and USD 23.53 for 40, 60 and 80 Mg/ha biochar, respectively, while the cost of biochar used for this experiment was USD 85.33. The payback period for doses of 40 and 60 Mg/ha was estimated to be three years. With a carbon sequestration subsidy of USD 30 per ton of CO2, the use of biochar may be profitable in the first year of soybean production. This is the first comprehensive economic analysis of the use of biochar in soybean production in Poland and one of the few published worldwide.